Early evidence from South Carolina's Medicare-Medicaid dual-eligible financial alignment initiative: an observational study to understand who enrolled, and whether the program improved health? - Brian K. Chen; Y. Tony Yang; Rachelle Gajadhar (BMC, 2018)
Abstract Background Individuals dually eligible for Medicare and Medicaid coverage are among the sickest patients in the United States. Prior literature has identified a lack of care coordination or even conflicts of interest between the two programs as barriers to more efficient care and better health outcomes among dual-eligibles. The purpose of this study is to assess characteristics of dual eligibles who participated in South Carolina's 2015 voluntary Medicare-Medicaid financial alignment demonstration project, and to evaluate whether their participation led to better observable health outcomes. Methods We obtained all inpatient and emergency department visits, and all Medicaid outpatient visits of individuals identified as Medicare-Medicaid dual eligibles from 2011 to 2016 from South Carolina's Revenue and Fiscal Affairs Office. We employed logistic regressions to assess the characteristics of participants and quitters in the Medicare-Medicaid financial alignment demonstration project. To evaluate the impact of participation on health outcomes, we used an event study analysis that examines trends in outcomes over time, with participation in the demonstration project as the triggering event, and a difference-in-differences methodology that compares changes in health outcomes before and after participation in the demonstration project compared with a control group. Results Urban patients, female patients, and patients with heart problems, social and mental disorders, and importantly, patients with multiple comorbidities (as indicated by a higher Charlson comorbidity index) are less likely to join South Carolina's demonstration project. Once having joined, female patients and patients with a higher Charlson index appear to be more likely to quit. Those who joined did not appear to enjoy better health outcomes in the short time frame. Conclusions Policy makers should explore and address reasons why dual eligibles with complex health problems hesitate to join the alignment project, and continue to monitor whether such a program improves health given that a prolonged period of exposure to the program may be required to achieve better health among the nation's most vulnerable patients.